MODEL PEMEKARAN WILAYAH YANG MENYEJAHTERAKAN MASYARAKAT (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Expansion of area is intended to overcome the problem of administrative, political, economic, social,Â cultural, and defense security faced by the autonomous regions as a result of environmental changes.Â However, in reality in Indonesia, not least Expansion of area actually cause new problems. Many ofÂ the new autonomous regions are not able to fnance themselves, boundary dispute, local citizen confictÂ with new citizen because they do not agree combined with â€œother communityâ€, and seizure of naturalÂ resources. Normative reference in the form of Law No. 32/2004 on Regional Governance and RegulationÂ No. 129 of 2000 on Expansion Area, during this itâ€™s read by the local elite as an opportunity to expandÂ their region not as a responsibility to realize what is a noble goal of expansion area. Opportunities areÂ interpreted by the elites as an opportunity to gain some benefts, such as the existence of new positionsÂ in the executive and legislative environment. Therefore, necessary to formulate a model of area by usingÂ democratic procedures, which open opportunities formation of a new area based on local demand, soÂ participate, going from the bottom, and welfare of the people.Keywords : Area expansion, welfare of the people